CHARACTERISTICS OF PRIAPISM PATIENTS AT ARIFIN ACHMAD HOSPITAL RIAU PERIOD 2017-2021 - Yashar, Muhammad Adan; Permata sari, Wulan; Zamzami, Zuhirman; Jaya, Indra (Indonesian Urological Association, 2025)
Objective: To find out the description of the characteristics of Priapism patients. Material & Methods: This research used a total priapism patients in Arifin Achmad Hospital, Riau Province from January 2023 to February 2023. Results: From 7 patients with priapism who met the inclusion and exclusion criteria, most age group were from the 36-45 year age group in 3 (42.9%) patients. History of disease in patients with most priapism was leukemia in 3(42.9%) patients. Conclusion: Classification of ischemic priapism were in 4 (57.1%) patients and non-ischemic priapism was 3 (42.9%) patients and all management of priapism patients was carried out by surgery (100%). Keywords: Priapism, leukemia, management of priapism.